On the impact of renewable energy support schemes on power prices - Sven Bode (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2006)
Power production from renewable energies is supported through special support schemes in almost all industrialised countries. This is because they are generally not competitive today although their use offers a number of benefits that are not considered by energy markets. These support schemes need to be financed, though. Two main options can be observed: Either support through the general public budget or through a renewable energy mark-up that is charged to final power consumers. As this mark-up increases power costs for consumers, the support schemes have been criticised, especially by power intensive industries. It argues that it looses competitiveness on the world marked with higher electricity costs due to the mark-up. However, this argument is short-sighted as it only reflects one side of the medal, namely the mark-up. The increased used of renewable energies may also have an influence on the power price on the whole sale market. Based on the analysis of a specific case in Germany the present paper analyses this impact on the whole market more generally. Assuming a simple power market, I show that the power costs for consumers may decrease due to the support scheme. If and to what extend power costs decrease depends on the specific characteristics of the market and the value attached to the greenness of power from renewable energies.
Keywords: H23; L94; Q28; Q41; 330; Renewable energy suppport schemes